Kajian Nilai Sosial dan Moral pada Film Jumbo sebagai Materi Ajar Menulis Teks Drama di SMK - Fransisca Diah Ayu Putri Risma; Kundharu Saddhono (Universitas Palan, 2026)
This study examines the social and moral values contained in the Indonesian film Jumbo and their relevance as teaching materials for writing drama texts for eleventh-grade senior high school students. The background of this research is the need for contextual and value-based learning resources to support students’ drama writing skills. This study aims to identify social and moral values in the film and explain their applicability in drama writing instruction. A qualitative descriptive method with a literary analysis approach was employed. The data consist of dialogues, scenes, and conflicts in the film, collected through observation and documentation techniques. The findings reveal eighteen data of social values and twelve data of moral values, reflected through character interactions and ethical choices. These values are relevant for developing conflicts, characters, and messages in drama texts. This study concludes that Jumbo can serve as an effective and meaningful teaching material to enhance students’ drama writing skills and support character education.